European standards applied by administrative courts in resolving cross-border problems of citizenship and transcription of civil status certificates - Chmielarz-Grochal, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The cases concerning transcription of a child’s foreign birth certificate, in which the registered parents are persons of the same sex, as well as confirmation of Polish citizenship by such a child, have been in the field of judicial cognition of Polish administrative courts for just several years. The issue of admissibility registering same-sex couples as parents of a child in Polish registry office has gained the great importance in the context of shaping social and family relations and the role of positive law as their regulator in dynamic society. When deciding such, the courts face the necessity to resolve not solely conflicts of norms (principles and values) within the domestic law, but also conflicts of legal systems. In the process of judicial application of law there is a need for balancing – on the one hand – the principle of the protection of the rights of a child, and – on the other one – other principles basic to the Polish legal order, i.e. the fundamental principles of the socio-political system (especially the principle of protection of marriage as a liaison of a men and a woman as well as the protection of family, motherhood and parenthood that arise from the art. 18 of Polish Constitution) and the general principles governing particular areas of civil, family and procedural law. The child’s welfare is a general constitutional clause that shall be interpreted with the reference to the constitutional axiology and to the entire legal system. The protection the child’s best interests is also the overriding principle of the Polish family law, and governs all of the regulations in the area of relations between parents and children. The important and delicate nature of this matter caused the discrepancies in the jurisprudence due to admissibility of such transcription in the light of the public order clause. The panel of seven judges of the Supreme Administrative Court, in Resolution No. II OPS 1/19, determined that Polish law did not allow the transcription of a foreign birth certificate showing same-sex persons as parents.